2019
DOI: 10.1080/15563650.2019.1590586
|View full text |Cite
|
Sign up to set email alerts
|

A review of 4652 exposures to liquid laundry detergent capsules reported to the United Kingdom National Poisons Information Service 2008–2018

Abstract: Introduction: Liquid laundry detergent capsules contain concentrated liquid laundry detergent in a water-soluble polyvinyl alcohol membrane. Objective: To review 4652 exposures reported to the United Kingdom National Poisons Information Service (NPIS) and to assess the impact of regulatory changes on potential toxicity. Methods: Telephone enquiries to the NPIS and returned questionnaires for these products were analyzed for the period January 2008 to December 2018. Results: Data on 4652 exposures were reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…1,11 This is in contrast to the results of the current study, in which no corrosive or ulcerative lesions were noted on physical examination. Endoscopic or bronchoscopic exams were not performed on any of the patients in the current study, so it is possible that some lesions were 2 Smith et al found that although ingestion of pod detergent may cause some esophageal injury, none of their patients had oral erythema, ulcers, or swelling that indicated the need for endoscopy. 15 Altogether, the research evidence might best be understood as indicating little or no effect of pod detergent on the stomach and intestines, although clearly more research is needed into this possibility.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…1,11 This is in contrast to the results of the current study, in which no corrosive or ulcerative lesions were noted on physical examination. Endoscopic or bronchoscopic exams were not performed on any of the patients in the current study, so it is possible that some lesions were 2 Smith et al found that although ingestion of pod detergent may cause some esophageal injury, none of their patients had oral erythema, ulcers, or swelling that indicated the need for endoscopy. 15 Altogether, the research evidence might best be understood as indicating little or no effect of pod detergent on the stomach and intestines, although clearly more research is needed into this possibility.…”
Section: Discussionmentioning
confidence: 80%
“…In Europe, these liquid detergents most commonly contain anionic surfactants (20-35% per capsule), non-ionic surfactants (10-20%), propylene glycol (8-20%), and ethanol (2-5%) and have a pH of 7 to 9. 2,3 Based on various Safety Data Sheets (SDS) in the United States, the pod detergent compositions are similar to those in Europe. [4][5][6] After pods were launched in Europe, pediatric patients were reported to develop more severe reactions from oral exposure to these pods as opposed to traditional laundry detergent.…”
mentioning
confidence: 99%
“…Several exposure routes exist in the context of detergents and children, including ingestion, skin contact, and ocular exposure. Ingestion of detergent may lead to numerous systemic features including dyspnea, vomiting, diarrhea, and central nervous system depression [ 1 ]. Severe reactions may lead to pneumonitis, pharyngeal swelling, and upper airway inflammation requiring intensive care.…”
mentioning
confidence: 99%
“…Skin contact may result in rashes, blisters, and burns. The face is most commonly involved, followed by the hands and fingers [ 1 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation